Static axion stars revisited - Bautista, Brandon; Degollado, Juan Carlos (Frontiers in Astronomy and Space Sciences, 2024)
We consider static solutions to the spherically symmetric Einstein Scalar field systems with an axion potential known as axion stars originally described by Guerra, Macedo and Pani [1]. We construct numerically families of axion stars in the ground state, for different values of the decay constant fa. It is shown that the existence diagram becomes richer than the mini boson star case and several regions of stability appear as the value of fa decreases yielding to more massive configurations with larger compactness. Some intrinsic properties such as isotropy and compactness of such stars are also discussed. Finally we describe the motion of test particles around these objects.